Gender Agreement Attraction in Russian: Production and Comprehension Evidence - Slioussar, Natalia; Malko, Anton (Frontiers in Psychology, 2016)
Agreement attraction errors (such as the number error in the example “The key to the cabinets are rusty”) have been the object of many studies in the last twenty years. So far, almost all production experiments and all comprehension experiments looked at binary features (primarily at number in Germanic, Romance and some other languages, in several cases at gender in Romance languages). Among other things, it was noted that both in production and in comprehension, attraction effects are much stronger for some feature combinations than for the others: they can be observed in the sentences with singular heads and plural dependent nouns (e.g. “The key to the cabinets…”), but not in the sentences with plural heads and singular dependent nouns (e.g. “The keys to the cabinet…”). Almost all proposed explanations of this asymmetry appeal to feature markedness, but existing findings do not allow teasing different approaches to markedness apart. We report the results of four experiments (one on production and three on comprehension) studying subject-verb gender agreement in Russian, a language with three genders. Firstly, we found attraction effects both in production and in comprehension, but, unlike in the case of number agreement, they were not parallel (in production, feminine gender triggered strongest effects, while neuter triggered weakest effects, while in comprehension, masculine triggered weakest effects). Secondly, in the comprehension experiments attraction was observed for all dependent noun genders, but only for a subset of head noun genders. This goes against the traditional assumption that the features of the dependent noun are crucial for attraction, showing the features of the head are more important. We demonstrate that this approach can be extended to previous findings on attraction and that there exists other evidence for it. In total, these findings let us reconsider the question which properties of features are crucial for agreement attraction in production and in comprehension.